The books of Ezra and Nehemiah - Harrington, Hannah K. (New International Commentary on the Old Testament (NICOT), 2022)
Intro -- Title Page -- Copyright -- Contents -- List of Excursuses -- General Editor's Preface -- List of Abbreviations -- Bibliography -- Introduction to Ezra and Nehemiah -- I. The Text -- A. Language -- B. Sources -- C. Sections -- 1. Ezra Memoir -- 2. Nehemiah Memoir -- 3. Prologue -- D. Canonicity -- II. Date -- A. Order -- B. Ezra-Nehemiah and Chronicles -- C. Separate Authorship Theory -- D. Compilation -- III. Methodology -- IV. Setting -- A. Yehud -- B. Jerusalem -- C. Literary Criticism -- 1. Themes and Purpose -- 2. Literary Techniques -- 3. Literature and History -- D. Social Science -- V. Persian Rule -- A. History vs. Historicity -- B. Cyrus II (559-530 BCE) -- 1. The Conquests of Cyrus -- 2. The Jews under Cyrus's Rule -- C. Darius I (522-485 BCE) -- 1. The Reign of Darius I -- 2. The Jews under Darius I -- D. Artaxerxes I (465-424 BCE) -- 1. Artaxerxes Longimanus I -- 2. Artaxerxes and Ezra -- 3. Artaxerxes and Nehemiah -- E. Internal Jewish Leadership -- VI. Second Temple Judaism -- A. Monotheism -- B. Torah -- 1. Torah for Everyone -- 2. Heritage: What Was Ezra's Torah? -- 3. Legacy -- C. Sanctuary: The Second Temple -- D. Holy People -- VII. Christian Application -- VIII. Outline -- The Book of EZRA -- Text and Commentary -- I. From Babylonian Exiles to Temple Community (1:1-6:22) -- A. Return to Jerusalem (1:1-2:70) -- 1. Preparation for Return (1:1-11) -- a. Imperial Authorization (1:1-4) -- b. Enthusiastic Response and Financial Support (1:5-6) -- c. Return of the Sacred Vessels (1:7-11) -- 2. Genealogical Record of the Returnees (2:1-70) -- a. Returnees by Descent (2:1-20) -- b. Returnees by City (2:21-35) -- c. Temple and Related Personnel (2:36-58) -- d. Undocumented Israelites/Priests (2:59-63) -- e. Total Returnees and Animals (2:64-67) -- f. Financial Donations and Conclusion (2:68-70).